A bioinspired microreactor with interfacial regulation for maximizing selectivity in a catalytic reaction. Issue 58 (16th June 2020) - Han, Chenhui; Xu, Haolan; Waclawik, Eric R.; Li, Xin-Hao; Xu, Jingsan
Abstract : A cell-inspired microreactor can modulate the phase-oriented transport of reagents at interfaces, affording a powerful tool to optimize reaction selectivity. Abstract : We report a bioinspired emulsion microreactor composed of an electrical double layer to mimic the functions of cell membranes. This "artificial cell" can modulate the phase-oriented transport of reagents at the oil–liquid interface via the electrical double layer, affording a powerful tool to optimize the selectivity in a catalytic reaction.